Unveiling autism spectrum disorder in South East Asia through a public health Lens - Kumar, Alok; Bhattacharya, Sudip (Frontiers in Child and Adolescent Psychiatry, 2024)
Autism spectrum disorder (ASD) is a multifaceted developmental condition characterized by persistent challenges in social communication, restricted interests, and repetitive behaviors. Though there is no cure, early and intensive interventions can significantly improve the quality of life for those affected. The aim of this paper is to examine the complexities of autism spectrum disorder (ASD) from a public health perspective in South East Asian region, highlighting the global rise in prevalence and the compounded challenges posed by the COVID-19 pandemic. The rise in ASD prevalence from 4 to 5 cases per 10,000 children in the 1980s to 11.3 per 1,000 children in 2012 highlights the need for effective interventions. The pandemic exacerbated behavioral issues, anxiety, and screen time-related health problems, underscoring the importance of adjusting strategies for early identification and support. Diagnostic tools like the Modified Checklist for Autism in Toddlers (M-CHAT) and the Social Communication Questionnaire (SCQ) play a critical role in community-based screening. Effective prevention strategies include primary measures such as public awareness campaigns and genetic counseling, secondary measures focusing on early identification and intervention, and tertiary measures involving ongoing support and therapy. Addressing implementation challenges, particularly in low-income countries, requires enhanced public awareness, training of community health workers, and integration of ASD services into primary healthcare systems. Future research should aim to develop and evaluate scalable, culturally relevant interventions and explore the impact of environmental factors on ASD. Comprehensive strategies at the community level, combined with robust public health policies, are crucial for improving outcomes for individuals with ASD and their families.